Different stages of chronic kidney disease are associated with physical performance in adults over 60 years - Song, Peiyu; Xu, Xinghong; Zhao, Yinjiao; Gu, Minghong; Chen, Xiaoyu; Zhang, Hui; Wu, Xinze; Yu, Chen; Niu, Jianying; Ding, Wei; Zhang, Suhua; Guo, Qi (Frontiers in Public Health, 2022)
Objective: The purpose of this study was to determine the association between different stages of chronic kidney disease (CKD) and sarcopenia and its components in the Chinese older population. Methods: The study comprised of 2213 participants aged ≥ 60 years (1025 men; mean age: 70.7 years) recruited from Shanghai who were invited to participate in a comprehensive geriatric assessment. Sarcopenia was defined according to the AWGS 2019 consensus update on sarcopenia diagnosis criteria. The glomerular filtration rate (GFR) was estimated using the equation that originated from the CKD-EPI equation, and patients with eGFR ≥ 90 mL/min/1.73 m2 were classified as normal and CKD 1, eGFR between 60 and 89 mL/min/1.73 m2 as CKD 2, eGFR between 15 and 59 mL/min/1.73 m2 as CKD 3-4, and eGFR <15 mL/min/1.73 m2 as CKD 5, kidney failure. Results: The overall prevalence of sarcopenia was 19.0%, which increased with the severity of CKD. The prevalence of sarcopenia in patients with CKD 3-4 and kidney failure was significantly higher than that in normal and CKD 1-2 (p < 0.05). In logistic regression analysis model, compared with normal and CKD 1 patients, kidney failure was significantly associated with the increased risk of sarcopenia and low grip strength(p<0.05); CKD 2, CKD 3-4 and kidney failure groups were significantly associated with an increased risk of low walking speed (p<0.05), respectively; while the association between CKD and muscle mass was not shown. Conclusions: In our study, the risk of sarcopenia increased with the severity of CKD, and the severity of CKD was more related to muscle function than muscle mass. This may improve the evidence for the prevention and intervention of sarcopenia in patients with CKD.